2004
DOI: 10.1073/pnas.0308133100
|View full text |Cite
|
Sign up to set email alerts
|

Differential recruitment of nuclear receptor coactivators may determine alternative RNA splice site choice in target genes

Abstract: The biological consequences of steroid hormone-mediated transcriptional activation of target genes might be difficult to predict because alternative splicing of a single neosynthesized precursor RNA can result in production of different protein isoforms with opposite biological activities. Therefore, an important question to address is the manner in which steroid hormones affect the splicing of their target gene transcripts. In this report, we demonstrate that individual steroid hormones had different and oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 33 publications
5
86
0
Order By: Relevance
“…Consistent with this, animal studies have indicated a role for androgens and estrogen in prostate vascularization (Daehlin et al 1985). In this context, it is interesting to note that nuclear receptor-coregulator complexes can regulate splicing events (Auboeuf et al 2002(Auboeuf et al , 2004. Thus, a role for the aberrant recruitment of nuclear receptor complexes to the VEGF promoter in the induction of pro-angiogenic VEGF splicing during carcinogenesis cannot be excluded (Fig.…”
Section: Transcriptional Regulation Of Pro-angiogenesis Pathways In Pcamentioning
confidence: 78%
“…Consistent with this, animal studies have indicated a role for androgens and estrogen in prostate vascularization (Daehlin et al 1985). In this context, it is interesting to note that nuclear receptor-coregulator complexes can regulate splicing events (Auboeuf et al 2002(Auboeuf et al , 2004. Thus, a role for the aberrant recruitment of nuclear receptor complexes to the VEGF promoter in the induction of pro-angiogenic VEGF splicing during carcinogenesis cannot be excluded (Fig.…”
Section: Transcriptional Regulation Of Pro-angiogenesis Pathways In Pcamentioning
confidence: 78%
“…In addition, transcriptional coregulators of the nuclear receptor family recruited at the promoter level not only enhances the transcriptional activity of this promoter, but also affects the nature of the splice variants produced. [28][29][30] Moreover, some transcription factors have been reported to bind to proteins of the spliceosome and/or display dual functions in splicing and transcription. [31][32] Taken together, these results indicate a function for proteins controlling transcription in splicing regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-E2F1 (C-20), anti-SC35 (H-55) and anti-Bcl-x L (H5) antibodies were purchased from Santa Cruz, the anti-Bcl-x S (Ab-1) from Oncogene Research, the anti-E2F1 (KH95) and anti-procaspase-3 from Pharmingen, the anti-FLIP (NF6) from Alexis, the anti-actin (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) from Sigma, the anti-SC35 (4F-11) from Euromedex and the anti-SRp20 (7B4) and anti-SF2/ASF from Zymed. Cleaved caspase-3 (Asp175) was from Cell Signaling.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, steroid hormones have been previously described as controlling alternative premessenger-RNA splicing. 45,46 For instance, the alternatively spliced isoforms of the CD44 gene are regulated in breast tumor cells in which each isoform may play a particular role in time and space. 47 We may hypothesize that such specific factor(s) affecting HLA-G splicing may be upregulated according to the physiopathological context and related microenvironment.…”
Section: Discussionmentioning
confidence: 99%